DAMPAK PSIKOLOGIS KEKERASAN DALAM RUMAH TANGGA TERHADAP PERKEMBANGAN EMOSIONAL ANAK - Luqman Rohmad Maghribi; Eko Handoyo; Edi Waluyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Domestic violence (KDRT) experienced by children, both as direct victims and as witnesses, has a profound and lasting impact on their emotional development. The complex psychological effects include emotional disorders, anxiety, post-traumatic stress disorder (PTSD), depression, low self-esteem, and difficulty establishing healthy interpersonal relationships. This study aims to describe and analyze the psychological impact of domestic violence on children's emotional development. Using a qualitative descriptive method through a library research approach, data was collected from scientific journal articles, official policy documents, and relevant reference books published between 2018 and 2026. The results show that domestic violence significantly disrupts children's emotional regulation, triggers long-term behavioral disorders, and impairs cognitive and social development. Early detection, psychosocial intervention, and family ecosystem strengthening are identified as the main pillars of effective recovery. This study concludes that a multidisciplinary collaborative approach involving families, schools, and government institutions is essential for the holistic protection and recovery of child victims of domestic violence.